Penerapan Metode Saw (Simple Additive Weighting) Untuk Penilaian Peserta Lomba Da’i Di Pondok Putra Pesantren Tebuireng Berbasis Website - Asaduddin, Mu’ammar; Imam Agung, Achmad; Lazulfa, Indana (Inovate, 2022)
Structured assessment is a way that can be done to help the committee or the jury so that it is not wrong in assessing all participants of the Da'i competition in Pondok Putra Tebuireng Islamic Boarding School. Structured assessment can result in final scores that are very fair and accurate, so this race is a very fair and quality race. The purpose of this study is to assess the Da'i race participants fairly and accurately, so that the seeds of students who are superior in terms of da'wah are found. There are several criteria used for this assessment, namely the criteria of Rhetoric, Smoothness, Theme, Adab, and Age. The method used in this research is SAW (Simmpel Additive Weighting), that is, it is the existing method of Decision Support System. This method is a method with weighted addition terms. The basic concept of the SAW method that is, all attributes must find the weighted addition of the rating performance of each alternative The SAW method requires a normalization proces from the matrix decision (X) to a scale that can be stackup with each available rating. This research produces a website-based system, so that all users can access. The SPKKUDAIRENG system can be used to assess Da'i contestants at Pondok Putra Tebuireng Islamic Boarding School according to the rules formed by the SAW calculation process. Keywords: Simpple Additive Weighting, Da'i, Tebuireng, Website, Decision Support System